Evaluation of Different Organic Nutrient Sources on Growth and Yield of Foxtail Millet (Setaria italica) in Acidic Soils of Meghalaya - Reddy, Maram Bhargav; Hareesh, Dhara; Majumdar, Sabyasachi; Priya, Govindarajan Bhuvana; Sangappa (International Journal of Bio-resource and Stress Management, 2026)
The experiment was conducted during kharif (June to September) of 2024 at Umdiker village, Ri-Bhoi district, Meghalaya, India at a farmer’s field under the broader initiative of the Indian Institute of Millets Research (IIMR) to evaluate the response of foxtail millet (Setaria italica) to different organic inputs with respect to growth, yield performance, and soil health indicators. The experimental layout followed a randomized block design consisting of five replications and five treatments: Vermicompost, Poultry manure, CAU Bioenhancer, their respective combinations, and an untreated control. The application of these inputs allowed for assessment of their main and interactive effects on critical crop and soil parameters across a single growing season. Findings demonstrated that plots receiving poultry manure in combination with the CAU Bioenhancer produced the most favorable results for plant growth, yield components, and essential soil nutrients, closely followed by the combined application of vermicompost with the Bioenhancer. Both integrated treatments outperformed sole applications of poultry manure or vermicompost, with the control ranking last. Significantly, the integration of Bioenhancer with poultry manure or vermicompost led to observable increases in both grain yield (by 29%) and straw yield (by 36%) compared to the untreated control plots. Among soil parameters, improvements in organic carbon and nitrogen, phosphorous, potassium were noted as statistically significant under the integrated treatments; however, soil pH remained unaffected by any input. The results underscored the productivity and soil fertility benefits of coupling organic manures with bioenhancers in finger millet-based cropping systems in northeast India.